2004
DOI: 10.1590/s1413-78522004000400005
|View full text |Cite
|
Sign up to set email alerts
|

A operação de Sofield e Millar no tratamento da osteogênese imperfeita

Abstract: ARTIGO ORIGINAL / ORIGINAL ARTICLE RESUMOA osteogênese imperfeita é uma doença genética causada por um defeito do colágeno do tipo I. Os portadores caracterizam-se pela baixa estatura, escleras azuladas, deformidades esqueléticas e fragilidade óssea. Os autores analisam os resultados da operação de Sofield e Millar que foi realizada em 23 ossos acometidos em oito portadores de osteogênese imperfeita com deformidades e antecedentes de múltiplas fraturas. Após um seguimento médio de dez anos e dois meses, onze o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…(Figure 4) In Brazil, a telescopic intramedullary rod was developed by our team in 2000. Its creation was based on the principles of previous rods [7][8][9][10][11][12] , but now aiming at joint preservation as well as the Fassier-Duval rods' features. It was centrally attached into the distal epiphysis through its internal rod by means of a thread, and the trochanteric stabilization was achieved by the external rod through transosseous suturing of the greater trochanter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Figure 4) In Brazil, a telescopic intramedullary rod was developed by our team in 2000. Its creation was based on the principles of previous rods [7][8][9][10][11][12] , but now aiming at joint preservation as well as the Fassier-Duval rods' features. It was centrally attached into the distal epiphysis through its internal rod by means of a thread, and the trochanteric stabilization was achieved by the external rod through transosseous suturing of the greater trochanter.…”
Section: Discussionmentioning
confidence: 99%
“…3 For its surgical treatment, the use of telescopic intramedullary rods is recommended as the gold standard. [4][5][6][7][8][9][10][11][12] The objective of this study was to assess the effectiveness of the Fassier-Duval (FD) rod by conducting a retrospective analysis of patients with Osteogenesis Imperfecta operated by our team.…”
Section: Introductionmentioning
confidence: 99%
“…The complications observed in our patients are consistent with those reported in the literature; fracture and migration are complications inherent to the disease's evolution and the use of rods. 4,6,10,12,14,25,28,29,31,[36][37][38][39][40][41] The role of the fracture, as the main complication, is more evident if only rods monitored for more than ten years are analyzed. We agree with Azzam et al 31 who reported that non-surgical patients have a higher fracture rate.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, OI must be clinically treated using bisphosphonates to increase bone resistance and mineral density [17][18][19][20][21][22][23][24] . In moderate and severe cases where children present with excessive fractures or deformities, surgical treatment using intramedullary rods is recommended 3,10,[25][26][27] ,which aids in correcting these problems and facilitates the possibility of walking in severely affected patients, thus improving their quality of life 2,6,10,13,[27][28][29][30][31] . Telescopic rods have evident advantages, as they require fewer surgical interventions in response to children's growth compared with non-telescopic rods because of their ability to adapt to bone growth, serve as an internal template and prevent deformities 3,9,[32][33][34][35] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation